Spectrally Tunable Solid State Fluorescence and Room‐Temperature Phosphorescence of Carbon Dots Synthesized via Seeded Growth Method. Issue 9 (18th February 2019) - Zhu, Jinyang; Bai, Xue; Chen, Xu; Shao, He; Zhai, Yue; Pan, Gencai; Zhang, Hanzhuang; Ushakova, Elena V.; Zhang, Yu; Song, Hongwei; Rogach, Andrey L.
Abstract: A seeded growth method to produce colloidal carbon dots (CDs) through controlling the number of seeds and reaction time, which is demonstrated to be an effective way to tune their optical properties, is developed. Color‐tunable fluorescence of CDs with blue, green, yellow, and orange emissions under UV excitation is achieved by increasing the size of the seed CDs, with the color depending on the size of the π‐conjugated domains. Strong multicolor photoluminescence of powdered samples enables realization of efficient down‐conversion white‐light‐emitting devices with correlated color temperature ranging from 9579 to 2752 K and luminous efficacy from 19 to 51 lm W −1 . Moreover, color‐tunable room‐temperature phosphorescence of CD powders is demonstrated in the broad spectral range of 500–600 nm. It is related to the presence of the nitrogen‐containing groups at the surface of CDs, which form interparticle hydrogen bonds to protect the CD triplet states from quenching, and to the existence of the polyvinylpyrrolidone polymer chains at the surface of CDs. The color‐tunable room‐temperature phosphorescence from CDs demonstrated in this work exhibits potential for data encryption. Abstract : Both the number of seeds added to the reaction mixture and the reaction time affect the diameter of carbon dot samples, which is related to the degree of extent of their π‐conjugated domains, governing their emission color. The bottom part of the table of contents image shows photographs of the phosphorescent powders taken at different UV excitation delay times.